Creative Projects: A Less Routine Approach Toward Getting New Things Done - Obstfeld, David (Organization Science, 2012)
This paper presents a framework for action that accounts for both how organizations get routine things done and how they pursue markedly new things through “creative projects.” Based on this framework, organizational routines and creative projects are viewed as two types of action trajectories differing with respect to their repetitiveness. An ethnographic case study of an automotive prototype-purchasing process and two initiatives to redesign that process is used to compare an organizational routine with creative projects occurring within the same organizational setting and to further explicate the framework. Case analysis reveals how projection and planning, as well as combinatorial action, knowledge articulation, and contingency management, unfold differentially in organizational routines and creative projects. This paper contributes to our understanding of different forms of organizational change and innovation. It also provides a framework to examine the role of nonroutine organizing at several levels of organizational analysis and its relationship to more routine forms of organizing.